2022
DOI: 10.1080/23802359.2022.2044403
|View full text |Cite
|
Sign up to set email alerts
|

A mitochondrial genome assembly of the opal chimaera, Chimaera opalescens Luchetti, Iglésias et Sellos 2011, using PacBio HiFi long reads

Abstract: Chondrichthyans (sharks, rays and chimeras) are a fascinating and highly vulnerable group of early branching gnathostomes. However, they remain comparatively poorly sampled from the point of view of molecular resources, with deep water taxa being particularly data deficient. The development of long-read sequencing technologies enables the analysis of phylogenetic relationships through a precise and reliable assembly of complete mtDNA genomes. The sequencing and characterization of the complete mitogenome of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Chimaeridae includes species traditionally placed in the genera Chimaera and Hydrolagus (Figure 2; Figure S3). However, as in previous studies we fail to resolve the reciprocal monophyly of these genera (Figure S3) [34,49,75,76]. Instead, we resolve four major clades in Chimaeridae, two of which necessitate the resurrection of available generic names.…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…Chimaeridae includes species traditionally placed in the genera Chimaera and Hydrolagus (Figure 2; Figure S3). However, as in previous studies we fail to resolve the reciprocal monophyly of these genera (Figure S3) [34,49,75,76]. Instead, we resolve four major clades in Chimaeridae, two of which necessitate the resurrection of available generic names.…”
Section: Resultsmentioning
confidence: 50%
“…Using this approach, we were able to sample 100% of all living holocephalian genera and species complexes, including all three species in Callorhinchus, seven of the nine recognized species in Rhinochimaeridae, and 35 of 47 described species of Chimaeridae [40], plus two specimens of Chimaera sp. with mitogenomes that appear to diverge considerably from other species [48,49]. We concatenated these data into a single set of aligned sequences for subsequent phylogenetic analyses.…”
Section: (B) Morphological Dataset Constructionmentioning
confidence: 99%
“… 2021 ; Vilas-Arrondo et al. 2022 ). Hydrolagus and Chimera were also resolved as paraphyletic by the mitochondrial genome tree in the present study, which indicated the affinity of the two genera and the necessity of a comprehensive phylogenetic review.…”
Section: Resultsmentioning
confidence: 99%
“… 2001 ), OK638184 ( C. opalescens ) (Vilas-Arrondo et al. 2022 ), MT880605 ( Chimaera sp.) (unpublished), HM147138 ( C. fulva ) (Inoue et al.…”
Section: Resultsmentioning
confidence: 99%